Design and Implementation of a Computer Decision Support System for the Diagnosis and Management of Dementia Syndromes in Primary Care - Iliffe, S.; Austin, T.; Wilcock, J.; Bryans, M.; Turner, S.; Downs, M. (Methods of Information in Medicine, 2002)
Background: Diagnosis and management of dementia is a complex process and primary care physicians are under-equipped to deal with uncertainties in the provision of optimal care for the patient.Objective: To develop a computer decision support system (CDSS) which could assist physicians with diagnosis and management and improve patient care. Methods: A design group including general practitioners derived logic pathways for diagnosis and management of dementia and validated them with a multi-professional expert group. Logic pathways were used to construct a comprehensive CDSS rendered as a series of expert consultations. The CDSS was inserted into commercially available GP systems and bench and field-tested.Results: The complexity of dementia diagnosis and management can be captured in logic pathways which can be expressed as decision trees within existing electronic patient records. The resulting CDSS appears useable in routine practice.Conclusion: The impact of this CDSS will be evaluated in a randomised controlled trial of educational interventions in primary care.
Keywords: Computer-assisted decision support; dementia; primary care; diagnosis; case management